Konflik, Karakter dan Pancasila: Studi Kepustakaan - Sidik Puryanto (Mahesa Research Center, 2022)
The purpose of this study is to analyze the relationship between conflict and character in Indonesia, and Pancasila as a source of character for conflict resolution. As the largest pluralistic country in the world, Indonesia cannot be separated from conflict. History records many identity conflicts caused by ethnic conflicts, religious and racial differences, conflicts between groups, and increasingly strong ideological wars. This research method uses literature study. The resulting literature studies are sourced from books, articles, which are relevant to conflict, interaction, character. The results of this study are (1) conflict is caused by the intersection of character needs and interests; (2) the character of the conflict includes the attitudes, emotions, and habits of various people. Therefore, the effort that must be done is to revitalize the practice of Pancasila values. Pancasila as a spiritual value (the highest cosmos), as well as a moral value, must be implemented in everyday life, with the aim of preventing and resolving conflicts in the present and in the future.